Research Methods in Management Academic Programs: From Where we are to Where we Want to go - Silva, S.A.; Ramos, S. (12th European Conference on Research Methodology for Business and Management Studies ECRM 2013, 2013)
The purpose of management research is to develop valid knowledge to support thoughtful practitioners and organizational problem solving in the field (Huff et al., 2006; Saunders et al, 2009). Business and management research has a distinctive focus once management knowledge is sustained by contributes from other disciplines and research should be problem/practice oriented completing a cycle of theory and practice (e.g. Easterby-Smith et al., 2008; Tranfield & Starkey, 1998). Therefore, in the last years several authors emphasized the relevance of evidence-base management (e.g., Rousseau, 2006; Saunders et al., 2009). Considering these assumptions research methods courses assumes particular significance in Management Academic Degrees and it is important to characterize it current status. Departing from a curriculum analysis of management programs in different national and international universities, the present work intends to contribute for a reflection on the role of research methods courses in these programs. This analysis has two main purposes: to explore the presence and number of research methods courses and to explore its contents (which methods and techniques are covered). Management academic programs (bachelor and master) where examined, considering top management schools (according to Financial Times 2012 ranking) and national schools (the biggest and with better position on the national ranking). Specifically, 18 programs where covered (6 Portuguese universities, 8 European universities and 4 North American universities). Each program was analyzed focusing research methods courses presence and content. Analysis covered all the topics that are globally shared and that constitute the Contents of most referenced books. Preliminary results show a general low presence of methods’ courses on curricula, both in undergraduate and master level. It was also observed that the methods courses available to students show a clear predominance of quantitative methods over qualitative ones, with a high prevalence of statistics. The presence of methods on management teaching leads us to questioning its role, which acquires particular relevance within the functions of management. Indeed, the underrepresentation of methods is a problem if they are taken not only as useful research tools in strictly academic context but rather as fundamental instruments for decision making, development of critical thinking, understanding relevant scientific information and designing projects to solve real problems in organizations.